Uttar Pradesh Tourism Report - Planning Commission 2002 - Planning Commission (Planning Commission, 2002)
The city of Agra is spread over an area of 120 sq.km, and has a population of about 1.2 million. This is projected to double by about 2031. on account of a large influx of domestic and international tourist and also on account of a daily influx of labour force from nearby areas, the city is estimated to have a floating population of about 20,000. This constitutes a tremendous pressure on the city infrastructure which has not been able to keep pace with the population growth. Consequently, the pressure has spilled on to the environment.
Planning Commission
Planning Commission